Development and refinement of the sore throat pain model as an assay for measuring therapeutic effects on acute pain - Schachtel, Bernard P.; Shephard, Adrian (Frontiers in Pain Research, 2025)
The physical and subjective status of patients with acute throat pain has been developed and refined over the past 40 years as an acute pain model to measure changes in patient-reported symptoms attributed to active pharmacologic intervention when patients with painful pharyngitis are evaluated under randomized, double-blind, placebo-controlled conditions. Acute, painful pharyngitis is a familiar experience for the majority of adults and children (“a sore throat” is the most common example of the aches and pains of the common cold). As such, the condition has served as a general acute pain model to demonstrate the acute effects of non-prescription-strength analgesic agents (for mild-to-moderate pain) and prescription-strength analgesics (for moderate-to-severe pain). Here we discuss the methodologic features of this clinical pharmacology assay as it was refined from its original examinations of classic, orally administered, acute analgesics (aspirin, acetaminophen, aspirin with caffeine, ibuprofen) to its more recent evaluations of celecoxib, valdecoxib, topical benzydamine, and topical flurbiprofen.